Lainaksi vain - Katz, Esa; Ahlroos, Atte; Blomster, Nina; Ekebom, Eero; Gavrilenko, Jan; Holsti, Martti; Kanninen, Perttu; Niemelä, Nea; Rintala, Janne; Uljas, Piia; Veijonen, Mikko (Eska, 2003)
10 kappaletta.